ECO-ACTIVITY PEMBELAJARAN MENGENAL TANAMAN HERBAL PADA ANAK USIA DINI - Warih Anggi Pratiwi; Arip Prehatiningsih; Mahmuddah Dewi Edmawati; Raya Qoirun Fatqul Hidayah; Putri Ambar Arum Rozita Asri (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
This study aims to develop an eco-activity innovation for introducing herbal plants to children aged 5–6 years. The research employs a Research and Development (R&D) method using the 4-D development model, which includes the stages of define, design, develop, and disseminate. The research subjects consist of material and media expert validators, as well as users, namely teachers and early childhood students in several kindergartens in Sukoharjo Regency. Data collection techniques include questionnaires and documentation, while data analysis is conducted using descriptive quantitative and qualitative approaches, with validity testing using Aiken’s V.The results indicate that the developed eco-activity product focuses on activities introducing herbal plants to children, including making traditional herbal drinks (jamu) and planting herbal plants. Expert validation results show that Aiken’s V values range from 0.5 to 1.00, categorized as valid. Meanwhile, feasibility and practicality tests conducted by teachers obtained an average score of 4.9, categorized as highly feasible and highly practical. The implementation of the activities shows an increase in children’s understanding of the types, characteristics, and benefits of herbal plants, as well as the development of environmental awareness. In addition, children appear more active, enthusiastic, and directly involved in the learning process. Therefore, eco-activity can serve as an innovative and effective alternative learning activity to introduce environmental concepts from an early age through meaningful hands-on experiences. ABSTRAK Penelitian ini bertujuan untuk mengembangkan inovasi eco-activity dalam pengenalan tanaman herbal pada anak usia 5–6 tahun. Penelitian menggunakan metode Research and Development (R&D) dengan model pengembangan 4-D yang meliputi tahap define, design, develop, dan disseminate. Subjek penelitian terdiri atas validator ahli materi dan media, serta pengguna yaitu guru dan anak usia dini di beberapa Taman Kanak-Kanak di Kabupaten Sukoharjo. Teknik pengumpulan data menggunakan kuesioner dan dokumentasi, sedangkan analisis data dilakukan secara deskriptif kuantitatif dan kualitatif dengan uji validitas menggunakan Aiken’s V. Hasil penelitian menunjukkan bahwa produk yang dikembangkan eco-activity kegiatan mengenal tanaman herbal pada anak, kegiatannya membuat jamu dan menamam tanaman herbal. Hasil validasi ahli menunjukkan nilai Aiken’s V verada pada angka 0.5 – 1.00 pada kategori valid, sedangkan uji kelayakan dan kepraktisan oleh guru memperoleh rata-rata skor 4,9 dengan kategori sangat layak dan sangat praktis. Implementasi kegiatan menunjukkan adanya peningkatan pemahaman anak terhadap jenis, ciri, dan manfaat tanaman herbal, serta tumbuhnya sikap peduli lingkungan. Selain itu, anak terlihat lebih aktif, antusias, dan terlibat langsung dalam proses pembelajaran. Eco-activity dapat menjadi alternatif aktivitas pembelajaran inovatif yang efektif dalam mengenalkan konsep lingkungan hidup sejak dini melalui pengalaman langsung yang bermakna.